2018
DOI: 10.1177/0011392118765213
|View full text |Cite
|
Sign up to set email alerts
|

Care migration: The connectivity between care chains, care circulation and transnational social inequality

Abstract: One of the features of the global commodification of care is the outsourcing of care work to migrants. The aim of this article is to investigate theoretical responses to the incorporation of migrant care workers in transnational care arrangements. After a description of the scope of migrant care labour and the global care economy, the article summarizes the challenges posed by this empirical phenomenon and asks to what extent care migrations on a global scale have common denominators. The author discusses thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 41 publications
2
21
0
16
Order By: Relevance
“…Similar to the findings presented in the theme perceptions on class asymmetries , previous research has shown that the migrant care and domestic sectors are often marked by a high degree of social and economic inequality [ 105 , 106 , 107 , 108 ]. Employers frequently discriminate against and justify paying migrant care and domestic workers low wages based on their gender, ethnicity, social class, religion and nationality [ 89 , 107 , 109 , 110 ].…”
Section: Discussionsupporting
confidence: 81%
“…Similar to the findings presented in the theme perceptions on class asymmetries , previous research has shown that the migrant care and domestic sectors are often marked by a high degree of social and economic inequality [ 105 , 106 , 107 , 108 ]. Employers frequently discriminate against and justify paying migrant care and domestic workers low wages based on their gender, ethnicity, social class, religion and nationality [ 89 , 107 , 109 , 110 ].…”
Section: Discussionsupporting
confidence: 81%
“…When migration becomes a major link between different components of care systems, gender equality considerations multiply. Macro-level inequali-ties related to the differences in wealth in societies of the Global South and the Global North, and most recently of the old and the new member states of the EU, are interlinked with micro-level inequalities within the family as well as between caregivers and care receivers (Lutz, 2018;van Hooren, Apitzsch, & Ledoux, 2019). As a consequence, care work is embedded in complex hierarchies and power relations between the employer and the employee, the carer and the cared, and the citizens and the migrant workers of a country, and thus mirrors inequalities linked to gender and various other grounds, including ethnicity, nationality, race, and citizenship status.…”
Section: Introductionmentioning
confidence: 99%
“…For some migrant workers, the contact with family members is reduced to digital connectivity and temporary visits. This is what Lutz (2018) claims are the emerging emotional and care inequalities of transnational care giving.…”
Section: Egalitarian Ideologies On the Movementioning
confidence: 86%